The Effectiveness and Stability Test of Moisturizing Cream Extracts of Fruit Peel Papaya (Carica papaya L) and Rambutan Nephelium lappaceum L) - Kartika Sari; Abu Dzarrin Al Ghifari; Teti Indrawati; Shelly Taurhesia; Dhanella Cristy (Jurnal EduHealth, 2022)
The skin of the fruit that has not been used by humans and other living things so far, has a fairly good nutritional value for the skin. The purpose of this study was to determine the effectiveness and stability of the moisturizing cream. Fruit peel papaya and fruit peel rambutan were extracted respectively using ethanol 70% by maceration method, produced maserate, concentrated using a rotary evaporator. The combination of extracts was made into a cream preparation using the emulsification method. The resulting cream was evaluated for stability and effectiveness in humans. Skin moisture test showed that the increase in skin moisture value occurred in all formulas, where the highest percentage value was seen in F4, namely the initial moisture value of 46.99±3.908 and after 28 days of use it became 58.95±3.792 there was an increase in skin moisture value of 11 ,96, while in F1 as a positive control the results of the skin moisture value before use of 46.98 ± 4.634 and after using for 29 days it became 53.61 ± 4,888 there was an increase in skin moisture value of 6.63. The resulting cream is stable on storage for 3 months at temperatures of 250 and 400